(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Clinical phenotypes and mortality rates of alcoholic liver cirrhosis in patients with previous COVID-19 infection. This study investigated the clinical phenotypes and mortality outcomes in patients with alcoholic liver cirrhosis (ALC) and a history of COVID-19 infection. A retrospective-prospective observational study was conducted between 2022 and 2024 at the Bukhara Regional Clinical Hospital. A total of 120 patients were analyzed: 68 with prior COVID-19 infection and 52 as controls. The findings revealed that ALC patients with COVID-19 had higher rates of Child-Pugh C (46% vs. 25%, p=0.02), higher MELD scores (19.3 ± 5.2 vs. 15.1 ± 4.7, p=0.01), and increased mortality (35.3% vs. 17.3%, p=0.03). These results suggest that COVID-19 aggravates the clinical course of alcoholic liver cirrhosis, leading to more severe phenotypes and higher mortality.